Artificial Intelligence (AI) Model Development Framework For The Protection Of State Borders, With A Focus On Analyzing Behavioral Patterns (Global Journal of Computer Science and Technology, 2024)
This study explores the development and implementation of an artificial intelligence AI model designed to predict illegal border crossing locations thereby enhancing the effectiveness of national border security measures By integrating and analyzing diverse data sources - including satellite imagery social media and environmental factors - this AI model aims to identify potential migration patterns and high-risk areas for illegal crossing This research highlights the model s ability to provide real-time risk assessments offering a novel approach to border security that surpasses traditional methods in terms of both efficiency and cost-effectiveness The model s adaptability continuous learning capabilities and user-friendly interfaces ensure its relevance in addressing contemporary border-security challenges This article contributes to the ongoing discourse on the application of AI in national security by proposing a solution that leverages technology for improved coordination among immigration services government organizations and international bodies
Keywords: artificial intelligence; software engineering; border security; illegal migration; risk assessment